Natural, human and spatial constraints to expanding populations of otters in the Iberian Peninsula - Clavero, Miguel; Hermoso, Virgilio; Brotons, Lluís; Delibes, Miguel (Journal of Biogeography, 2010)
Aim To determine the relationships between otter (Lutra lutra) distribution dynamics and environmental and spatial constraints over a 20-year period. Location Andalusia, southern Iberian Peninsula. Methods We synthesized otter distribution data from three otter surveys (1985, 1995 and 2005) using subcatchment areas defined by hydrological barriers. Subcatchments were characterized by two ‘natural’ (climatic and orographic variables) and two ‘human’ (land use and population density) gradients. In addition, we calculated two contagion variables (the distance to previously occupied subcatchments and the percentage of occupied subcatchments within a 50 km buffer) for consecutively surveyed subcatchments. Results Between 1985 and 2005 the percentage of subcatchments with otters present increased from 42% to 72%. Otters tended to be rare or absent from human-dominated areas. Anthropogenic gradients were better predictors of otter distribution than natural ones. Human and natural gradients showed strong covariation, but for any value of the natural gradients otters tended to be present in subcatchments with lower human impacts. Colonization of new subcatchments was found to be strongly related to contagion variables and expansion rates were slower than those estimated in other studies. Newly colonized areas tended to be located in areas with intermediate human influence, while repeated absences occurred mainly in areas where human impact was most severe. Main conclusions Our results suggest that recent otter expansion across Andalusia is a reflection of large-scale improvement in environmental conditions. Otter populations that survived the period of strong and generalized declines appear to be acting as sources from which neighbouring areas are colonized, probably aided by improved water quality and increases in food availability. However, the further expansion of otters into their full original range is likely to be constrained by human-impacted landscapes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Andalusia; freshwater environments; landscape gradients; Lutra lutra; mammals; Mediterranean streams; otter surveys; recolonization; recovering species

Spatial pattern of adult trees and the mammal-generated seed rain in the Iberian pear - Fedriani, Jose M.; Wiegand, Thorsten; Delibes, Miguel (Ecography, 2010)

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José M.; Delibes, Miguel (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.
Keywords: Global environmental change; monitoring; National Park conservation; NDVI; Remote sensing.

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José M; Delibes, Miguel (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.
Keywords: Global environmental change; monitoring; National Park conservation; NDVI; Remote sensing.